The Degree to Which Educational Supervisors Practice Creative Supervision in the State of Kuwait: A Teachers' Perspective - حسن أحمد الطعاني; عبدالرحمن الهاجري (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study aimed to identify the extent to which educational supervisors practice creative supervision from the teachers' perspective in the State of Kuwait. Methods: The study sample consisted of 400 male and female teachers in the State of Kuwait, selected using a stratified random method. A tool was developed with 37 items, and its validity and reliability were verified. Results: The study concluded that educational supervisors' practice of creative supervision was at a high level. The results also indicated that there were no statistically significant differences in the degree of educational supervisors' practice of creative supervision based on gender and academic qualification. Furthermore, there were no statistically significant differences based on years of experience, except in the field of training courses where differences favored those with 10 years of experience or more. Conclusions: The study suggests the need to enhance the creative supervision skills of educational supervisors in the State of Kuwait.